ChemInform Abstract: Thermodynamic Description of the Layered O3 and O2 Structural LiCoO2‐CoO2 Pseudo‐Binary Systems. Issue 36 (9th September 2014) - Chang, Keke; Hallstedt, Bengt; Music, Denis; Fischer, Julian; Ziebert, Carlos; Ulrich, Sven; Seifert, Hans J.
Abstract Review: 49 refs.